First-principles study of Mn antisite defect in Li2MnO3. (5th August 2021) - Zhang, Shiwei; Wang, Jianchuan; Lei, Ting; Li, Xu; Liu, Yuling; Guo, Fangyu; Wang, Jun; Zhang, Weibin; Dang, Feng; Seifert, Hans; Sun, Lixian; Du, Yong
Abstract: Lithium-rich layered Li2 MnO3 is regarded as a new generation cathode material for lithium-ion batteries because of its high energy density. Due to the different preparation methods and technological parameters, there are a lot of intrinsic defects in Li2 MnO3 . One frequently observed defect in experiments is Mn antisite defect (MnLi ). In this work, we study the energetics and electronic properties involving MnLi in Li2 MnO3 through first-principles calculations. We find that MnLi can reduce the formation energy of Li vacancies around it, but increase that of O vacancies, indicating that MnLi could suppress the release of O around it and facilitate capacity retention. Both O and Mn near the MnLi can participate in charge compensation in the delithiation process. Furthermore, the effect of MnLi on the migration of Li and Mn is investigated. All possible migration paths are considered and it is found that MnLi makes the diffusion energy barrier of Li increased, but the diffusion energy barriers of Mn from transition metal layer to Li layer are decreased, especially for the migration of the defect Mn. The insight into the defect properties of MnLi makes further contribution to understand the relationship between intrinsic defects and electrochemical properties of Li2 MnO3 .